Complex Ureteral Reconstruction via Open or Robotic Ureteroplasty with a Buccal Mucosa Onlay Graft: A Two-center Comparison - Antonio Andrea Grosso; Fabrizio Di Maida; Daniele Paganelli; Simon Udo Engelmann; Emily Rinderknecht; Christoph Eckl; Sebastian Kälble; Alexey Barskov; Rino Oriti; Sofia Giudici; Christoph Pickl; Maximilian Burger; et al. (European Urology Open Science)
Background and objective: Management of a long proximal ureteral stricture is challenging. Buccal mucosal graft (BMG) ureteroplasty is a reliable technique for ureteral reconstruction that avoids the morbidity of bowel interposition or autotransplantation. We compared open and robotic BMG ureteroplasty in a two-center study. Methods: We compared prospectively recorded data for 26 patients who underwent robotic or open BMG ureteroplasty at two academic institutions. Stricture location and length, previous reconstructive interventions, complications, and success rates were assessed and compared. A descriptive statistical analysis was performed. Key findings and limitations: We compared ten patients in the robotic group and 16 in the open group. Stricture location had similar distributions in the open versus robotic group (pelvic junction, 25% vs 20%; proximal ureter, 56.3% vs 60%; middle ureter, 18.7% vs 20%). Median stricture length was significantly longer in the robotic group (26 vs 17 mm; p = 0.01). The rate of previous reconstructive interventions was higher in the robotic group (80% vs 37.5%; p = 0.001). However, previous reconstructive interventions were more complex for the open surgery group. There were no intraoperative complications, and postoperative complication rates were similar in the open and robotic groups (18.7% vs 20%; p = 0.19). Median intraoperative blood loss was significantly lower in the robotic group (300 vs 175 ml; p = 0.03). The success rate was 93.7% in the open group and 90.0% in robotic group. Conclusions and clinical implications: We observed high success rates and low perioperative morbidity for both open and robotic BMG ureteroplasty. The robotic approach was associated with significantly lower intraoperative blood loss. Patient summary: Narrowing of the ureter, which is the tube draining urine from the kidney into the bladder, may need surgical treatment. For reconstruction of long segments, use of a tissue graft from the inside of the mouth is an effective surgical option. Robot-assisted surgery is as safe as open surgery and is associated with lower blood loss.